2020
DOI: 10.1093/sleep/zsaa014
|View full text |Cite
|
Sign up to set email alerts
|

Modeling sleep onset misperception in insomnia

Abstract: Objectives To extend and validate a previously suggested model of the influence of uninterrupted sleep bouts on sleep onset misperception in a large independent data set. Methods Polysomnograms and sleep diaries of 139 insomnia patients and 92 controls were included. We modeled subjective sleep onset as the start of the first uninterrupted sleep fragment longer than Ls minutes, where parameter Ls reflects the minimum length o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 24 publications
2
19
0
Order By: Relevance
“…In a previous study, we applied the model to PSG data from people with insomnia and healthy controls, testing different model assumptions (Hermans et al 2020a). We found a median optimal parameter L of approximately 30-35 min for participants with insomnia, with small variations depending on subgroup characteristics (Hermans et al 2020a). The optimal parameter L for an individual was referred to as Sleep Fragment Perception Index (SFPI).…”
Section: Estimating Subjective Sleep Onset From Sleep Fragmentationmentioning
confidence: 99%
See 4 more Smart Citations
“…In a previous study, we applied the model to PSG data from people with insomnia and healthy controls, testing different model assumptions (Hermans et al 2020a). We found a median optimal parameter L of approximately 30-35 min for participants with insomnia, with small variations depending on subgroup characteristics (Hermans et al 2020a). The optimal parameter L for an individual was referred to as Sleep Fragment Perception Index (SFPI).…”
Section: Estimating Subjective Sleep Onset From Sleep Fragmentationmentioning
confidence: 99%
“…Interruptions of sleep at the beginning of the night may influence the perception of the SOL, since the sensation of being asleep prior to awakening from non-rapid eye movement (NREM) sleep was shown to depend on the length of the preceding bout of uninterrupted sleep (Sewitch 1984;Bonnet and Moore 1982;Hauri and Olmstead 1983). In previous research, we quantified the relationship between sleep fragmentation at the beginning of the night and sleep onset (mis)perception and found that the perception of the sleep onset latency indeed seems particularly influenced by the length of uninterrupted sleep fragments (Hermans et al 2020a). Additionally, the objective and subjective numbers of awakenings have been shown to be correlated with measures of subjective sleep quality (Rosipal et al 2013;Kaplan et al 2018), providing an additional indication that sleep fragmentation may negatively influence sleep.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations